D DEMOCRACY, DEMOCRATISATION AND DEVELOPMENT IN NIGERIA: AN OVERVIEW - Udeoji, Ebele (Advances in Social Sciences Research Journal, 2020)
ABSTRACT Democracy and development are key concepts in the developmental discourse, and they are considered crucial to a sustainable developmental strategy. This study thus appraised the nexus between democracy and development in Nigeria. The study utilized content analysis and descriptive method to actualize the objectives of the research. This study revealed that absence of democratic paraphernalia like free and fair election, rule of law, constitutionalism among others, have constituted series of misunderstandings in the tenets and principles of liberal democracy, especially in Nigeria. The study further ascertained that factors such as: poor state of economy, high level of unemployment, illiteracy, ignorance, ethnicity, tribalism, ethno-religious crises, and poverty have coalesced to constitute impediments to the smooth and effective operation of democracy in Nigeria, with serious implications for democratization and sustainable development. Among others, the study recommends political, structural and institutional reforms of the Nigerian state in a manner that promote and deepen democracy and national development.